2020
DOI: 10.1177/1329878x20921568
|View full text |Cite
|
Sign up to set email alerts
|

Children’s perspectives and attitudes towards Fortnite ‘addiction’

Abstract: Playing digital games is increasingly pathologized as an addiction or a disorder, but there is limited research into the impact of game addiction discourse on children who play digital games. In this article, we present results from a study into the digital play of twenty-four 9–14-year-olds, attending to our participants’ perspectives and attitudes towards ‘game addiction’ and how it interacts with their play and identity. Focused primarily on the online multiplayer first-person shooter game Fortnite, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…For the most part our participants described a non-problematic desire to 'unlock' and 'earn' their skins within the allotted time frame, but these comments demonstrate the power that battle passes, and the structure they provide, has in shaping and configuring player experience in Fortnite. As we discuss elsewhere [2], our participants often struggled to negotiate the pervasive media panic about Fortnite as 'addictive' with their normal and healthy desires to play. As Cover [20] has previously discussed, the tension between when something is a hobby enthusiastically engaged in, versus a problematic behavior, is a key characteristic of videogame media panic.…”
Section: Seasons and Battle Passesmentioning
confidence: 95%
See 2 more Smart Citations
“…For the most part our participants described a non-problematic desire to 'unlock' and 'earn' their skins within the allotted time frame, but these comments demonstrate the power that battle passes, and the structure they provide, has in shaping and configuring player experience in Fortnite. As we discuss elsewhere [2], our participants often struggled to negotiate the pervasive media panic about Fortnite as 'addictive' with their normal and healthy desires to play. As Cover [20] has previously discussed, the tension between when something is a hobby enthusiastically engaged in, versus a problematic behavior, is a key characteristic of videogame media panic.…”
Section: Seasons and Battle Passesmentioning
confidence: 95%
“…Similarly, James (13, M) had tried the game once and didn't find it entertaining, but rather just a clone of popular battle royale game PUBG (which he notes, he also doesn't enjoy). There is a discourse around the game, one that is embedded within notions of addiction [2], but it is also more than that.…”
Section: Affective Sense Of Worldnessmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers found that children negotiate the discourses, which impact on their playing experiences and their identity as players. For instance, children use 'addiction' to describe their usual way of playing, whereas parents use the term 'pathology' to describe it (Carter et al, 2020b). Likewise, the authors propose that incorporating children's viewpoints into these discourses concerning 'problematic play' and their right to play is significant (Apperley, 2015(Apperley, , 2017.…”
Section: Conflicting Viewpoints Regarding the Use Of Movsmentioning
confidence: 99%
“…This idea echoes the Convention on the Rights of the Child's recognition of boys' and girls' right to play (OHCHR, 1990, article Nº31). In other work, Carter et al (2020b) argue that the appeal of Fortnite is linked to its intersection with YouTube and game live streaming, as well as how the game acts as a vehicle for social capital and identity performance, in addition to the rich social experience promoted by the game. These notions allow young people to participate in a vast repertoire of cultural and informational practices concerning the game (Carter et al, 2020b).…”
Section: Conflicting Viewpoints Regarding the Use Of Movsmentioning
confidence: 99%